Kajian Bentuk Fungsi dan Makna Upacara Ngusabha Dimel - I Made Novianta (Pramana: Jurnal Hasil Penelitian, 2022)
This study examines the form, function and meaning of the ngusaba dimel ceremony in the Batur Traditional Village which is an implementation unit related to carrying out ceremonies that are very unique and rarely found in other traditional villages. To study it, the author uses several theories, namely: (1) Symbol Theory (2) Religious Theory and (3) Structural Functional Theory. This study uses a qualitative approach with a location in the Batur Traditional Village. The type of data used is qualitative data with primary and secondary data sources. The ngusaba dimel ceremony in Batur Traditional Village, Kintamani District, Bangli Regency, from the process of implementing ngusabha dimel, found social functions with various meanings, namely magical religious meanings and sacred meanings.